FRAMEWORKING THE ISSUES OF LESBIAN GAY BISEXUAL TRANSGENDER (LGBT) AT MAGDALENE.CO (KALIBATA CITY ARTICLE: BETWEEN MUTILATION AND â€œSANCTUARYâ€) - Radjagukguk, Djudjur Luciana; Rahmah, Munzi Aulia (Journal of Social Political Sciences, 2021)
The raid on an LGBT party in August 2020 and then in Kuningan, South Jakarta became the main spotlight amid the hustle and bustle of the Covid-19 pandemic. The media coverage of the case was quite controversial. Because several media discriminate against LGBT people. However, Magdalene. co does not see LGBT people as oppressed and need to be heard. This paper analyzes how Magdalene framed LGBT issues in one of her articles entitled â€œKalibata City: Between Mutilation and 'Sanctuary'â€ through Robert N Entman's framing analysis approach to explaining how alternative media portrays sensitive issues such as LGBT in their writings. By using Robert N. Entman's framing analysis with the Define Problems, Diagnose Causes, Make Moral Judgment, and Treatment Recommendation methods, this study is expected to identify and analyze the framing of LGBT issues in the article. The result of this research is that the alternative media Magdalene. co framed LGBT people as oppressed and received unfair treatment so they need to be heard. On the aspect of defining the problem, Magdalene. co explained that LGBT people get discriminated against by the community. Diagnosing causes explain the cause of the discriminatory attitude because LGBT people are troubling citizens, and not following the norms that apply in society. In the aspect of making a moral judgment, Magdalene. co emphasizes that LGBT is negatively stigmatized by society and the aspect of treatment recommendation emphasizes that this problem will always exist.